2017
DOI: 10.3390/su10010054
|View full text |Cite
|
Sign up to set email alerts
|

Tourism as an Approach to Sustainable Rural Development in Post-Socialist Countries: A Comparative Study of Serbia and Slovenia

Abstract: Abstract:The research deals with the sustainable development of the Serbian and Slovenian countryside, under the influence of tourism progress. The article identifies the main rural tourism competitiveness in Serbia and Slovenia, as one of the essential factors of rural development in both countries, analyzing the main contributions and making a series of proposals to guide the future research agenda. The aim of the paper is to clarify around one obviously defined objective-to point out the competitiveness of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(84 citation statements)
references
References 53 publications
1
58
0
4
Order By: Relevance
“…Tourism is defined as "the sum of the phenomena and relationships resulting from travel and stay of non-residents" [5]. It is highly appreciated with the name of "smokeless industry" and prioritized as a crucial economic driving force [2]; and it is also called the "green economy" [6]. Everett and Aitchison [7] and Demirović et al [8] found a strong relationship between tourism and the local life, culture and heritage, while Petrović et al [9] discovered that tourism is closely related to natural attractions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tourism is defined as "the sum of the phenomena and relationships resulting from travel and stay of non-residents" [5]. It is highly appreciated with the name of "smokeless industry" and prioritized as a crucial economic driving force [2]; and it is also called the "green economy" [6]. Everett and Aitchison [7] and Demirović et al [8] found a strong relationship between tourism and the local life, culture and heritage, while Petrović et al [9] discovered that tourism is closely related to natural attractions.…”
Section: Introductionmentioning
confidence: 99%
“…Everett and Aitchison [7] and Demirović et al [8] found a strong relationship between tourism and the local life, culture and heritage, while Petrović et al [9] discovered that tourism is closely related to natural attractions. As a consequence, tourism can improve the national identity [6] and bring huge benefits to society [10].…”
Section: Introductionmentioning
confidence: 99%
“…Fertile chernozem soils (over 40% of the world reserves), a variety of climatic, geomorphological, landscape conditions predetermine the paramount importance of highly efficient agro-industrial clusters in our country [18,28] with further transformation of existing types of environmental management into knowledge-intensive and hitech productions [11]. Their efficiency may increase manyfold if combined with agroecotourism and other types of recreational environmental management [22]. It is difficult to overestimate the role of clusters for the development of rural territories [19,26].…”
Section: First Attempts Of Clustering In Russiamentioning
confidence: 99%
“…and after 2000, transition begun, but burdensome and already late (Lazić & Cvejić, 2011). The development of tourism in Serbia in the context of the restructuring of transition economies has received some limited research attention (Bjeljac, Brankov, Jovičić, Ćurčić, & Terzić, 2013;Dwyer, Dragićević, Armenski, Mihalič, & Knežević Cvelbar, 2016;Mulec & Wise, 2013;Petrović, Blešić, Vujko, & Gajić, 2017;Petrović et al, 2018), but this research has not previously taken a cultural perspective. Thus, this paper aims to analyze the impact of the GLOBE culture dimensions on the emergence of entrepreneurial activities in the Serbian municipality of Lazarevac, home to the industrial giant of the "Kolubara" coal mine.…”
Section: Introductionmentioning
confidence: 99%